PRELIMINARY EXPERIMENTAL DATA PROCESSING IN STATISTICAL IC DESIGN - P. G. Pavlov; T. T. Tran; A. I. Kostrov; V. V. Nelayev; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of researches on a choice and implementation of mathematical methods of the preliminary analysis and statistical processing of experimental data are presented. Data are received at processing and interpretation of industrial measurements of results from integrated circuits production. This technique allows not only to exclude the abnormal observations in the sample data, but also to carry out the procedure of smoothing the results of measurements or simulations.